Metformin-dolutegravir interaction leads to metformin-associated lactic acidosis: A case report - Zaawari, Abdullah; Varma, Muralidhar; Tirlangi, Praveen Kumar; Harsha, Mutthineni; Avvaru, Deepthi (Indian Journal of Case Reports, 2024)
Metformin, a biguanide, is considered the standard first-line drug for managing type 2 diabetes mellitus (T2DM) patients owing to its safety profile. Despite having a highly safe profile, it is capable of causing serious adverse effects. Biguanides decrease gluconeogenesis from alanine, pyruvate, and lactate, which may result in lactic acidosis. The risk is high in patients with polypharmacy or comorbidities. This is a case of a 48-year-old Indian female with a known case of human immunodeficiency virus (HIV), T2DM, hypothyroidism, and hypertension who presented to the hospital with progressive right-sided weakness for the past 10 days along with transit loss of vision. The patient was diagnosed with multiple central nervous system tuberculomas, for which antitubercular treatment and dexamethasone were started. The patient was on a tenofovir, lamivudine, and dolutegravir regimen for HIV. The patient was started on metformin for sugar control, which led to metformin-associated lactic acidosis. A drug interaction between dolutegravir and metformin was attributed to this. The patient improved after metformin was replaced with glipizide, and lactate levels returned to normal. Lactic acidosis is a rare side effect of metformin. However, the risk of lactic acidosis is high when another drug interferes with metformin pharmacokinetics. Proper assessment and evaluation of potential drug–drug interactions is crucial to assure safe and effective therapy.